2016
DOI: 10.1016/j.ahj.2016.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes of renal function in relation to ace inhibitor/angiotensin receptor blocker dosing in patients with heart failure and chronic kidney disease

Abstract: Fröhlich, H. et al. (2016) Long-term changes of renal function in relation to ace inhibitor/angiotensin receptor blocker dosing in patients with heart failure and chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
1
16
1
Order By: Relevance
“…ACE and ACE2 play different roles in RAS; ACE generates Angiotensin II, whereas ACE2 is a negative regulator of the system, decreasing Angiotensin II (Crackower et al 2002). The abnormal increase of Angiotensin II was reported mostly associated with hypertension and heart failures (Packer and McMurray, 2017), and sometimes also lung and renal dysfunctions (Fröhlich et al, 2016;Kuba et al, 2005; 2017; Torres et al, 2014). We measured the plasma level of Angiotensin II from 2019-nCoV infected patients and healthy individuals, the plasma levels of Angiotensin II from 2019-nCoV infected patients were significantly higher than that of healthy individuals ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…ACE and ACE2 play different roles in RAS; ACE generates Angiotensin II, whereas ACE2 is a negative regulator of the system, decreasing Angiotensin II (Crackower et al 2002). The abnormal increase of Angiotensin II was reported mostly associated with hypertension and heart failures (Packer and McMurray, 2017), and sometimes also lung and renal dysfunctions (Fröhlich et al, 2016;Kuba et al, 2005; 2017; Torres et al, 2014). We measured the plasma level of Angiotensin II from 2019-nCoV infected patients and healthy individuals, the plasma levels of Angiotensin II from 2019-nCoV infected patients were significantly higher than that of healthy individuals ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…The present study showed insignificant difference between patients with and those without CKD based on the administration of NSAID or/and ACEI/ARBs. Still, ACEI/ARBs were classified as renoprotective based on criteria that depend on the degree of renal dysfunction, renal function response and presence of comorbidities (Frohlich et al 2016). ACE inhibitors have showed the ability to reduce progression of ESKD compared with a placebo group, but no statistical significant was found between ACE inhibitors and other antihypertensive monotherapies such as ARBs, B blockers or calcium channel blockers regarding developing risk for ESKD, mortality and clinical vascular and renal outcomes (Steventon et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be explained by their exclusion of CKD stage 5 and dialysis patients and the fact that their follow-up period was fixed at 12 months. 7 The varying follow-up period in our study meant that a proportion of patients was at early stages of medication optimization. With regard to other possible factors affecting medication optimization, our study showed that severity of CKD and nature of HF did not have an influence on the likelihood of successful initiation or dose up-titration similar to a study by Heywood et al 2 Risk of hyperkalaemia in patients with successful RAASi dose up-titration in our study was comparable to that reported in clinical trials.…”
Section: Figurementioning
confidence: 96%